Propueta de un modelo de monitoreo para definir la calidad hídrica de ecosistema - humedales, en el Parque Nacional Cotopaxí, Laguana de Limpiopungo. - Caiza Gatia, Edison Paul (2017)
The research work has been carried out with the application of different methodologies and research techniques being the primordial descriptive research and qualitative research with fundamental tools, because through it was able to interpret the results, field research indispensable for making Samples and the collection of basic information of the area under study; Being essential each of the methods and techniques applied for the diagnosis of the water quality of the wetlands of the lake Limpiopungo National Park Cotopaxi, presenting itself as the most productive and beneficial ecosystems of the planet, besides being among the most threatened by human activities . In wetlands, water and land are found to create the home of endless species of flora and fauna, and to harbor and maintain some of the environmental goods and services necessary for the survival and sustainable development of people. Stop it to say that wetlands are the beginning of 99% of the water that humans consume on the planet. Keywords: Wetlands, monitoring, ecosystems, desiccation.